2020
DOI: 10.18280/ijht.380205
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Heat Transfer Enhancement of Turbulent Flow Using Twisted Tape Insert Fitted with Hemispherical Extruded Surface

Abstract: Heat transfer enhancement of heat exchangers is an important matter of concern to achieve more effective thermal energy conversion systems. The use of modified twisted tape (TT) inserts as passive technique of heat transfer augmentation are effective way to improve heat transfer. In this study, a numerical analysis is performed to investigate the heat transfer performance enhancement and flow behavior in a circular pipe using TT insert fitted with a hemispherical extruded surface (HES). The study is carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The authors showed that the shell-side heat transfer coefficient increases from 9.3 to 25.5%, and the pressure drop is reduced from 15.3 to 47.1% compared to using a segmental baffle. Fazlay et al [22] numerically investigated the performance of the TH and the flow structure in a circular tube using a twisted tape insert equipped with a THS. The results show that the TT insert favors the vortex regime, which significantly increases the heat transfer rate than an ordinary tube.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the shell-side heat transfer coefficient increases from 9.3 to 25.5%, and the pressure drop is reduced from 15.3 to 47.1% compared to using a segmental baffle. Fazlay et al [22] numerically investigated the performance of the TH and the flow structure in a circular tube using a twisted tape insert equipped with a THS. The results show that the TT insert favors the vortex regime, which significantly increases the heat transfer rate than an ordinary tube.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the thermal mixing performance of hot and cold fluid mixing in intersecting and colliding type converging T-junctions has been investigated numerically by assuming incompressibility of fluid and realizable k-ε turbulence model. This k-ε turbulence model with two equations is widely used in industrial applications [26,27]. This K-ε model is proved to produce satisfactory results [3] This model was selected due to a good performance in flows which possesses strong gradients in temperature or pressure, separation, and recirculation due to turbulence [28].…”
Section: Introductionmentioning
confidence: 99%
“…Range. Fazlay Rubbi et al [12] performed the numerical study to research HT performance increasing and flow behavior in a circular tube using twisted tape insert fitted with HES. The results show that for twisted tape insert with hemispherical extrude surface lead to increase in heat transfer rate above 69.4% compared to plain pipe due to effective vortex flow and best mixing caused by the TT insert.…”
Section: Introductionmentioning
confidence: 99%